From Invisibility to Equality? Women Workers and the Gendering of Workers’ Compensation in Ontario, 1900–2005 - Storey, Robert (Labour / Le Travail, 2009)
Abstract The advent of a modern workmen’s compensation system in Ontario in the mid-1910s was a moment of significant gain for injured workers. With the passage of the 1915 Workmen’s Compensation Act (WCA), injured workers would no longer have to rely on an uncertain, even hostile, judge and jury system to receive some form of compensation from their employers. The WCA was, however, a gendered, i.e., discriminatory, statute. As the paper outlines, the 1915 WCA statutorily enshrined the assumptions of the day that women’s paid work was of less value than that of men’s. The situation remained uncontested until the 1970s, when a vibrant and politically influential injured workers’ movement (IWM) emerged and, in small but important ways, began to challenge the gendered and racialized dimensions of the worker’s compensation system. As it happened, the victories secured at this juncture by the IWM that impacted on women – both as injured workers and as wives, mothers, and widows of injured workers – proved to be more symbolic than material. For while a 1982 change in the name from “Workmen’s” to “Workers Compensation Act” was symbolic of a formally gender neutral statute (continued with the passage of the Workplace Safety and Insurance Act in 1997), women workers injured over the past two decades report that their claims are being processed by WCB officials who downplay the severity and the legitimacy of their injuries, on the one hand, and who circumscribe rehabilitation and job training programs with gendered notions that their jobs are secondary in importance to that of male members of their households, on the other hand. No longer totally ignored, injured women workers now confront a neo-liberal, increasingly welfarized workers’ compensation system whose formal gender neutrality does not address entrenched labour market inequalities or the regulatory and processual discrepancies between laws and their application.